Same meat, different gravy: ignore the new names of mycobacteria. Issue 1 (11th July 2019) - Tortoli, Enrico; Brown-Elliott, Barbara A.; Chalmers, James D.; Cirillo, Daniela M.; Daley, Charles L.; Emler, Stefan; Floto, R. Andres; Garcia, Maria J.; Hoefsloot, Wouter; Koh, Won-Jung; Lange, Christoph; Loebinger, Michael; et al.
In a recent article, Gupta et al. [1] have proposed a revision of the taxonomy of mycobacteria with the redistribution of 150 species of the genus Mycobacterium into five different genera; the four newly proposed genera hosting the nontuberculous mycobacteria (NTM) are called Mycobacteroides, Mycolicibacter, Mycolicibacterium and Mycolicibacillus . The proposed taxonomy is based on the theory of synapomorphies, molecular markers that most likely appeared early in an ancestor and then were vertically transmitted to descendants [2]. The detection of a number of such molecular markers, represented either by specific amino acid insertions/deletions or by whole proteins, selectively present in evolutionary-related groups of species, clearly depicts five major clades within the conventional genus Mycobacterium . The work is mostly sound and the emerging phylogeny impressively overlaps the ones originated by other phylogenomic approaches [3, 4]. The novelty is that Gupta et al. [1] have suggested to assign to each of these clades the status of independent genera. A new name for most Mycobacterium species has been recently proposed. According to taxonomic rules novel and previous nomenclature coexist and are synonyms. The use of the latter has the advantage of avoiding confusion for healthcare and harm for patients. http://bit.ly/2XhTACc